The Role of Islam in the Indonesian Foreign Policy in the Era of Joko Widodo’s Government (2014-2024): between the Islamic Identity and the National Interests - Damayanti, Rizki; Al Hasan, Khalid Ibrahim (JURNAL INDO-ISLAMIKA, 2024)
This research explores the role of Islam in Indonesian foreign policy during the era of Joko Widodo's government (2014-2024), examining the delicate balance between Islamic identity and national interests. This study focuses on analyzing how the Indonesian government utilizes its Islamic identity as a tool in shaping Indonesian foreign policy narratives and strategies on the international level. Drawing upon the theoretical framework of international relations and political Islam, this research employs a qualitative methodology. Data collection involves a comprehensive academic literature review, official government documents, media reports, and interviews with relevant stakeholders. The findings of this research shed light on the complex interplay between the Islamic identity and the national interests in shaping the Indonesian foreign policy during the Joko Widodo government era (2014- 2024). It reveals how some Islamic principles inform the Indonesian government's diplomatic engagements and international relations strategies while highlighting the tensions and synergies between Islamic values and broader national objectives.